2004
DOI: 10.1243/1350650042128021
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the thermal mixing in journal bearings

Abstract: Flows in the thermal mixing zone of a journal bearing are investigated using the computational fluid dynamics (CFD) approach. The complexity and inertial effect of the flows inside the supply region of different configurations are considered. It is shown that these flows are highly recirculating but have almost negligible effects on the thermal mixing. The turbulent flow inside the supply region is modelled using the k-ω turbulence model. Most parts of the supply region are filled with recirculation zones and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
3
7
0
Order By: Relevance
“…A fixed value of 0.1 has been selected after a brief parametric study. This small mixing coefficient is in agreement with the CFD study of Kosasih and Tieu [36], which concluded that although the flows occurring within the groove interior are highly recirculating, they have almost negligible effects on thermal mixing.…”
Section: Groove Regionssupporting
confidence: 90%
See 1 more Smart Citation
“…A fixed value of 0.1 has been selected after a brief parametric study. This small mixing coefficient is in agreement with the CFD study of Kosasih and Tieu [36], which concluded that although the flows occurring within the groove interior are highly recirculating, they have almost negligible effects on thermal mixing.…”
Section: Groove Regionssupporting
confidence: 90%
“…A higher than usual value of 750 W/m 2 K was chosen for H gr . Such value appears to be in better agreement with the highly recirculating flow found within groove regions [36,39] and indeed this allowed to replicate the strong temperature fade found experimentally in the vicinity of grooves [24].…”
Section: Conditions At the Interfacessupporting
confidence: 83%
“…However, when grooves start to interfere with the pressure profile, those models will be inadequate as they will not provide a rigorous treatment of groove mixing and other phenomena taking place at the vicinity of grooves. Examples of such complex -2 -phenomena are the mixing of hot lubricant coming from upstream of the groove with fresh lubricant [9] [10] and the occurrence of reverse flow of lubricant re-entering the groove from downstream or the backflow of groove lubricant flowing upstream in the direction opposite to the journal rotation [11] [12].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of what actually happens within the whole groove was carried out by Kosasih and Tieu . They used commercial CFD packages in order to investigate the thermal mixing occurring with different groove geometries.…”
Section: Introductionmentioning
confidence: 99%